2007
DOI: 10.1007/s11306-007-0063-5
|View full text |Cite
|
Sign up to set email alerts
|

Serum metabolomics reveals many novel metabolic markers of heart failure, including pseudouridine and 2-oxoglutarate

Abstract: There is intense interest in the identification of novel biomarkers which improve the diagnosis of heart failure. Serum samples from 52 patients with systolic heart failure (EF < 40% plus signs and symptoms of failure) and 57 controls were analyzed by gas chromatography -time of flight -mass spectrometry and the raw data reduced to 272 statistically robust metabolite peaks. 38 peaks showed a significant difference between case and control (p < 5·10 )5 ). Two such metabolites were pseudouridine, a modified nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
107
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(112 citation statements)
references
References 64 publications
(56 reference statements)
2
107
0
3
Order By: Relevance
“…A study of 52 patients with HF and 57 controls demonstrated differences in pseudouridine (modified nucleotide), 2-oxoglutarate (tricarboxylic acid cycle), 2-hydroxy 2-methylpropanoic acid, erythritol (a sugar alcohol), and 2,4,6-trihydroxypyrimidine between cases and controls. 274 Another study examined differences in urinary metabolites between HF cases and controls (n=15 and 20, respectively). 275 Urinary acetate and acetone were nominally higher in cases.…”
Section: Genomic Markers: Metabolomics and Genetic Proteonomic And mentioning
confidence: 99%
“…A study of 52 patients with HF and 57 controls demonstrated differences in pseudouridine (modified nucleotide), 2-oxoglutarate (tricarboxylic acid cycle), 2-hydroxy 2-methylpropanoic acid, erythritol (a sugar alcohol), and 2,4,6-trihydroxypyrimidine between cases and controls. 274 Another study examined differences in urinary metabolites between HF cases and controls (n=15 and 20, respectively). 275 Urinary acetate and acetone were nominally higher in cases.…”
Section: Genomic Markers: Metabolomics and Genetic Proteonomic And mentioning
confidence: 99%
“…In the study by Lin et al, 26 who used the same techniques as our study, the metabolomic fingerprint was characterized by higher levels of acetoacetate and urea and by lower levels of threonine, glycine, ethanol, histidine, alanine and tyrosine, results which were significantly different from our heart failure patient population. In the study by Dunn et al, 27 who employed gas chromatography and mass spectrometry, pseudopurine and 2-oxoglutarate were identified as two good indicators of heart failure. These metabolites were different from those reported by Lin et al and in our studies.…”
Section: Discussionmentioning
confidence: 99%
“…These metabolites were different from those reported by Lin et al and in our studies. These results could be due to the different characteristics of patients investigated (Lin et al 26 analyzed end-stage heart failure patients just before transplantation) or to the different samples analysis technique performed (Dunn et al 27 used gas chromatography). It is possible to affirm that metabolomic approach is able to identify a fingerprint characterizing heart failure patients, but a univocal and reproducible pattern is still not emerged in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, greater than 90% of the KEGG metabolites have distinct elemental composition 13 so that they can be measured based upon the accurate mass and mass resolution without requiring ion dissociation. [14][15][16] Metabolomic analysis of serum and plasma has revealed panels of metabolites that distinguish patients with cardiovascular disease, 17 breast cancer, 18,19 Parkinson disease, 20 and diabetes 21 from control patients. This technique is able to differentiate between individuals despite intraindividual variation due to factors such as dietary intake.…”
mentioning
confidence: 99%